(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Memory function appearing in the Mori’s memory function formalism has been used to evaluate the Shear viscosity of Lennard - Jones (LJ) fluids. The functional form of this memory function depends upon the thermodynamic state and at the same time it may be mentioned that the memory function is derivable from a equation of motion for the development of time correlation function (TCF). The results so obtained are compared with Molecular Dynamics simulation results.